2022
DOI: 10.1002/ppul.26172
|View full text |Cite
|
Sign up to set email alerts
|

Development of mortality prediction models for infants with isolated, left‐sided congenital diaphragmatic hernia before and after birth

Abstract: Background: Mortality prediction of congenital diaphragmatic hernia (CDH) is essential for developing treatment strategies, including fetal therapy. Several researchers have reported prognostic factors for this rare but life-threatening condition; however, the optimal combination of prognostic factors remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The most widely used variable to stratify lung hypoplasia is prenatal measurement o/eLHR combined with liver position [ 19 ]. As one of the independent predictors of CDH death, more recent studies from large CDH treatment centers have confirmed that o/e LHR had good predictive efficacy and stable expression during pregnancy [ 19 22 ]. Specifically, the mean AUC of o/eLHR < 25% for predicting mortality in neonates with left-sided CDH was 0.73, with a specificity of 0.95 and a relatively low sensitivity of 0.45 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used variable to stratify lung hypoplasia is prenatal measurement o/eLHR combined with liver position [ 19 ]. As one of the independent predictors of CDH death, more recent studies from large CDH treatment centers have confirmed that o/e LHR had good predictive efficacy and stable expression during pregnancy [ 19 22 ]. Specifically, the mean AUC of o/eLHR < 25% for predicting mortality in neonates with left-sided CDH was 0.73, with a specificity of 0.95 and a relatively low sensitivity of 0.45 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%